Action Analysis for Ice, Wind and Electro Dynamic Loads in Spans with Arbitrary Wire Layout - I. I. Sergey; Y. V. Bladyko; Y. G. Panamarenka; B. D. Tsemekhman; V. E. Tarasov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2012)
The paper considers problems pertaining to design of electrical power transmission line spans and switchgears with flexible conductors with due account of wind, ice and electro-dynamic loads. Impact evaluation assesses an influence of inter-phase insulating spacers on maximum rapprochement and tensile of flexible conductors at their electro-dynamic interaction.